Evaluating the Impact of the Inspiring School Program in High Schools: Reviewing Implementation and Educational Quality Enhancement - Putro, Hendro Yulius Suryo; Babiera, Rene M.; Takwin, Mukhlis; Rachman, Ali; Ariliani, Tiara (International Journal of Asian Education, 2024)
This research aims to evaluate the Inspirational School Program using the CIPP (Context, Input, Process, Product) model, focusing on providing insights and recommendations for enhancing its effectiveness and sustainability. Data collection methods in qualitative descriptive research include interviews, observation, and documentation. The study's sample population comprises individuals associated with SMA Negeri 5 in Banjarmasin, including educators, school leaders, and grade XI students. In-person interviews were conducted with the school principal, homeroom teacher, counselling teacher, and students. Data analysis techniques encompass data collection, reduction, presentation, and verification/conclusion. The results indicate that the school's needs align with the Ministry of Education and Culture guidelines. Despite limited local government support, the program planning and evaluation processes have been implemented effectively despite obstacles. The Product Evaluation Stage reflects positive outcomes, including literacy, numeracy, character development, and school safety climate improvements. Educator and staff competence have also seen enhancements. It is recommended to align implementation with the Independent Curriculum, bolster human resources through educator and staff training, enhance infrastructure support, and seek increased government assistance to sustain and improve the program. These measures aim to enhance productivity further and ensure the continued success of the Inspirational School Program.